Workplace wellness programs : services offered, participation, and incentives - Mattke, Soeren; Kapinos, Kandice A.; Caloyeras, John P.; Taylor, Erin; Batorsky, Benjamin; Liu, Hangsheng; Van Busum, Kristin R.; Newberry, Sydne J. (Research report (Rand Corporation), 2014)
This report leverages existing data on wellness programs to explore patterns of wellness program availability, employers' use of incentives, and program participation and utilization among employees. Researchers used two sets of data for this project: The first included data from the 2012 RAND Employer Survey, which used a nationally representative sample of U.S. employers that had detailed information on wellness program offerings, program uptake, incentive use, and employer characteristics. These data were used to answer questions on program availability, configuration, uptake, and incentive use. The second dataset included health care claims and wellness program information for a large employer. These data were analyzed to predict program participation and changes in utilization and health. The findings underscore the increasing prevalence of worksite wellness programs. About four-fifths of all U.S. employers with more than 1,000 employees are estimated to offer such programs. For those larger employers, program offerings cover a range of screening activities, interventions to encourage healthy lifestyles, and support for employees with manifest chronic conditions. Smaller employers, especially those with fewer than 100 employees, appear more reserved in their implementation of wellness programs. The use of financial incentives appears to increase employee participation in wellness programs, but only modestly. Employee participation in lifestyle management aspects of workplace wellness programs does not reduce healthcare utilization or cost regardless of whether we focus on higher-risk employees or those who are more engaged in the program.